Carryover effects of larval environment on individual variation in a facultatively diadromous fish. Issue 18 (20th August 2019) - Saboret, Grégoire; Ingram, Travis
Abstract: Intraspecific trait variation may result from "carryover effects" of variability of environments experienced at an earlier life stage. This phenomenon is particularly relevant in partially migrating populations composed of individuals with divergent early life histories. While many studies have addressed the causes of partial migration, few have investigated the consequences for between‐individual variability later in life. We studied carryover effects of larval environment in a facultatively diadromous New Zealand fish, Gobiomorphus cotidianus, along an estuarine salinity gradient. We investigated the implications of varying environmental conditions during this critical stage of ontogeny for adult phenotype. We inferred past environmental history of wild‐caught adult fish using otolith microchemistry (Sr/Ca) as a proxy for salinity. We tested for main and interactive effects of larval and adult environment on a suite of traits, including growth rates, behavior (exploration and activity), parasite load, and diet (stable isotopes and gut contents). We found a Sr/Ca consistent with a continuum from freshwater to brackish environments, and with different trajectories from juvenile to adult habitat. Fish with Sr/Ca indicating upstream migration were more vulnerable to trematode infection, suggesting a mismatch to freshwater habitat. Diet analysis suggested an interactive effect of larval and adult environments on trophic position and diet preference, while behavioral traits were unrelated to environment at any life stage. Growth rates did not seem to be affected by past environment. Overall, we show that early life environment can have multiple effects on adult performance and ecology, with the potential for lifetime fitness trade‐offs associated with life history. Our study highlights that even relatively minor variation in rearing conditions may be enough to generate individual variation in natural populations. Abstract : We investigated carryover effects of larval environment in a facultatively diadromous New Zealand fish, Gobiomorphus cotidianus . Using otolith microchemistry (Sr/Ca) as a proxy for salinity, we found that larval environment influence adult diet (stable isotopes and gut content) and parasitism, with a near significant effect on juvenile growth and no effect on adult behavior (exploration and activity).